STUDI EKSPERIMEN PENGARUH SUHU HARDENING DENGAN QUENCHING MEDIA AIR LAUT TERHADAP KETANGGUHAN BAJA ST 60 - Abdillah Halim; Muhammad Subhan; Zaldy Kurniawan (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
ST 60 steel is a medium carbon steel that is often used in machine construction such as shafts and shipbuilding, but impact loads often occur. The purpose of this study was to determine the best toughness of st60 steel from the effect of temperature on the hardening process. The method used for data processing in this study is the two way ANOVA method without interaction. The variables used in this study were temperature (900, 930, 950⁰C) and holding time (30, 60, 90 minutes). The best toughness results were obtained at a temperature of 900⁰C with a holding time of 30 minutes (2.5934 J/mm2) with the lowest toughness results were obtained at a temperature of 950⁰C and a holding time of 90 minutes was obtained at (2.5588 J/mm2).